2021
DOI: 10.3847/1538-4357/abc9c1
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Aspherical Ejecta Properties in Type Ia Supernovae: Progenitor Dependence and Applications to Progenitor Classification

Abstract: Several explosions of type Ia supernovae (SNe Ia) have been found to exhibit deviations from spherical symmetry upon closer inspection. Examples are the gamma-ray lines from SN 2014J as measured by INTEGRAL/SPI and morphology information from radioactive isotopes in older remnants such as Tycho. A systematic study of the effects of parameters such as ignition geometry and burning morphology in SNe Ia is still missing. We use a twodimensional hydrodynamics code with postprocessing nucleosynthesis and simulate t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 158 publications
(229 reference statements)
0
3
0
Order By: Relevance
“…SN 2014J is the only SN Ia in the last few decades which has been detected in γ-ray. Early gamma-ray signals around 10 days detected after explosion and the observed line velocity of 56 Co (Diehl et al 2015) has provided indication on the explosion asymmetry (Leung et al 2021b) (but also see Churazov et al (2015) for other interpretations).…”
Section: Observations and Motivationmentioning
confidence: 93%
“…SN 2014J is the only SN Ia in the last few decades which has been detected in γ-ray. Early gamma-ray signals around 10 days detected after explosion and the observed line velocity of 56 Co (Diehl et al 2015) has provided indication on the explosion asymmetry (Leung et al 2021b) (but also see Churazov et al (2015) for other interpretations).…”
Section: Observations and Motivationmentioning
confidence: 93%
“…The successful detonation is mainly limited to the heaviest core mass of M CO = 1.1 M e . In the context of a onedimensional problem, it is thus indicated that direct ignition of detonation on a helium envelope with 0.02 M e (to avoid conflicts to observational properties; Shen et al 2021;Woosley & Kasen 2011) is extremely difficult for the progenitors of M CO = 0.9-1.0 M e , which are favorable for normal SNe type Ia (Shigeyama et al 1992;Sim et al 2010;Woosley & Kasen 2011;Leung et al 2021).…”
Section: Progenitor Conditions For Ignitionmentioning
confidence: 99%
“…The shocked dense gas can also greatly enhance the X-ray flux. Although it does not necessarily rule out the factor of intrinsic explosion asymmetry (see, e.g., Ferrand et al 2019;Leung et al 2021, for application of using explosion asymmetry in constraining explosion mechanism), at least the ISM environment plays a significant role in the formation of the asymmetric morphology of SNR G306.3−0.9.…”
Section: Origin Of Asymmetrymentioning
confidence: 99%